Perdagangan Internasional dan HAM: Relasinya dengan Sustainable Development - Prakasa, Satria Unggul Wicaksana (Jurnal Hukum Novelty, 2018)
Industrialization and export and import activities between countries around the world in this era of globalization. the issue of sustainable development in which the trade also related with physical and environmental aspects, but also considers the benefits and security of the man himself. Many facts encountered that some cases were found, the non-compliance of transnational corporations to pay attention to the principles of human rights fulfillment. Legal issues raised: (1) provisions on international trade, environment, and human rights. (2) case analysis related to international trade, environment and human rights. The research method used statue approach, conceptual approach, and case approach. Research results: (1) Countries are expected an important role in securing how the effects of human rights violations resulting from international trade activities can be minimized in such a way through the principles to protect, and respect for the human rights of citizens. Thus, the public benefits from many international trade activities conducted by the state. as well as sustainable development is also realized through the principle of remedy for transnational corporations found to have done environmental damage and accompanied by human rights violations in its business activities. (2) In the cases presented, it has proved that transnational corporations directly commit human rights violations and environmental destruction, to threats to the state sovereignty process. This issue needs to be addressed in the enforcement of international legal mechanisms. In the extraterritorial courts decision, it is difficult for plaintiffs who are victims of justice and accountability for human rights violations and environmental damage.